THE MAIN GRAMMATICAL FEATURES OF TWO-PART SENTENCES IN CHINESE AND KAZAKH LANGUAGE (Journal of Oriental Studies, 2019)
In this article we comprehensively conducted the speshal between two-part sentences in Chinese and Kazakh languages. Chinese is SVO form - language, in chinese the verb is formed by peculiarities of forming verbal sentences. The are not any big morphological changes. In any case: “peculiarity remains + verb is the basis + result remains”. In sentences the subject, the object and adverbial modifier are placed before the predicate. The word - combination and word formation are formed by this way. As  long as the auxiliary word and prepositions form the member of the sentence. Therefore, the words tend to change places, members of the sentence are widely used. However, in both languages the role of the subject and predicate remains unchanged.Key words: Altai language system, inflected language, word order, verbal predicates, two-part struc- ture, an amorphous language.